Facile universal strategy of presenting multifunctional short peptides for customizing desired surfaces - Ruofei Lu; Bingyang Zhao; Kaiyuan Huo; Hao Liu; Yang Wang; Xingjie Zan; Siwang Hu (Journal of Nanobiotechnology)
Abstract Interfacial properties determine biomaterial performances, such as cell adhesion, signal exchange, and biomineralization, which affect the tissue repair cycle and efficiency of clinical applications. Peptides, as short protein sequences that have defined functionalities, are highly stable and easy to synthesize and have enormous potential to reshape interfacial properties. However, the lack of a universal strategy for presenting peptides on various substrates substantially hinders the application of peptides. In this study, we report a facile and universal strategy for customizing desired interfacial functionalities by a well-known layer-by-layer (LbL) technique through the assembly polyphenols with positively charged short peptide-coupling functional sequences. Polyphenol–peptide interactions were elucidated in detail by assembling polyphenols and peptides possessing different characteristics (charged, uncharged, hydrophobic, and sequence length) in combination with molecular dynamics simulations, and isothermal titration calorimetry further revealed the favorable enthalpy change due to electrostatic interactions is the main driving force for assembling peptides with polyphenols. LbL coatings assembled from polyphenols and positively charged peptides exhibited good substrate generalization, stability, cell proliferation, and antioxidant properties, when prepared as hollow capsules by sacrificing the template, exhibited significant pH and ultrasound stimulation responses, which could be suitable candidates for drug carriers. Most importantly, the LbL assembly strategy of positively charged peptides could be utilized to present various functional molecules (such as arginyl–glycyl–aspartic acid (RGD), a cell adhesion motif; CM15, an antibacterial peptide; and PEG, an antifouling surface) on various substrates for customizing desired surfaces. This study not only provides new insights into the understanding and regulation of interactions between proteins/peptides and polyphenols but also paves the way toward the interfacial functionalization of biomaterials.